Statistics for pyhsical sciences an introduction - Martin, B.R (Elservier, 2012)
A guide to the commonly used ideas and techniques in statistical analysis, as used in physical sciences, together with explanations of their origins. It steers a path between the extremes of a recipe of methods with a collection of useful formulas, and a full mathematical account of statistics.